Smartphone-Based Smart Village App For Digitizing Wanurejo Services To Support Village SDGs Achievement - Dian Fithra Permana; Nina Oktarina; Uswatun Hasanah; Angga Dwi Ardianto; Syaefa Habsyah Nur Maulida (Universitas Lambung Mangkurat, 2026)
Tourism villages that are inclusive, adaptive, and sustainable Wanurejo Tourism Village, located near Borobudur Temple in Magelang, Central Java, possesses remarkable potential in culture, nature, creative economy, and community-based tourism. However, challenges remain, including limited digital literacy, suboptimal tourism promotion, and manual village administration services. This community service program aimed to implement digital transformation by developing the “Smart Desa” (DEWI—Desa Wisata Wanurejo) Android application, which integrates public services, local MSME promotion, and tourism information. The service method used in the digitalization program for Wanurejo Tourism Village can be categorized as Participatory Action Research (PAR), as the entire process emphasizes active community involvement—from problem identification and planning to action and evaluation. A training module and Standard Operating Procedures (SOP) were developed to strengthen digital literacy and ensure sustainability. The results indicate that the Smart Desa application successfully digitalized at least five administrative services, engaged over 500 active users, and facilitated the participation of 20 MSMEs within six months. Digital literacy training improved community competence, with 70% of participants demonstrating enhanced skills. Digital promotion on social media increased the village account's followers by 5,000, boosting tourist visits and MSME transactions. Additionally, supporting infrastructure, such as Wi-Fi access points and digital information boards, was provided, while youth forums were established to manage digital content and tourism packages. This program demonstrates that digital transformation not only enhances service efficiency and transparency but also empowers communities, strengthens economic competitiveness, and fosters sustainable tourism development. The initiative aligns with SDGs 8, 9, and 11 and supports higher education performance indicators by involving lecturers, students, and the local community. Overall, Wanurejo Tourism Village has become a model for smart tourism pratices.